From Right to Left: How Bardella and french political actors Navigate TikTok Politics - Bombaci, Mael; Nespoli, Francesco; Mulargia, Simone (AoIR Selected Papers of Internet Research, 2026)
The French National Rally’s 2024 legislative campaign is an example of how political parties strategically leverage new media, to reconfigure political engagement especially among younger demographics. This study investigates the role of TikTok in political communication strategies during the 2024 French legislative campaign, with a particular focus on how the National Rally is reshaping its image through specific communicative approaches. Grounded in theories of politainment, political personalization, and pop politics, this research examines how the communication strategies of Jordan Bardella, Gabriel Attal (Renaissance), and Jean-Luc Mélenchon (La France Insoumise) engage with pop culture, highlighting both their divergences and points of convergence. The study employs audiovisual content analysis on 131 TikTok videos produced by these political actors during the campaign. The analysis examines how TikTok’s affordances are leveraged, including the use of viral sounds, meme-based engagement, and informal storytelling. It also explores several key dimensions to understand the interaction between pop culture and political communication. Findings suggest Bardella’s use of TikTok aligns closely with the logic of politainment, effectively merging traditional party values with contemporary digital communication practices. Unlike Attal and Mélenchon, whose strategies remain more traditional, Bardella leverages pop culture references, informal aesthetics, and emotional appeal to establish a relatable and community-oriented political presence. This study contributes to the growing body of literature on social media politainment by illustrating how TikTok redefines political interaction. Future research could explore cross-national comparisons to better understand how political leaders interpret and model political interaction with new generations.